2019
DOI: 10.1002/ptr.6449
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid‐rich guava seed oil: Safety and bioactivity

Abstract: Guava (Psidium guajava) is a widely consumed fruit and has been commercialized in markets. The seeds are by-products of the processing procedures performed by the commercial guava juice industry. They are considered a nutritional resource that has been poorly utilized as they contain essential fatty acids such as linoleic acid (LA) and phenolics in abundance. In the study, guava seed oil (GSO) was used, which was obtained by hexane extraction of guava seeds to determine composition and test toxicity, cell migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Notably, Eschscholtzxanthin is one of the red pigment carotenoids that is synthesized in the leaves of several plants as a response to photoinhibitory conditions during winter acclimation and displays antioxidant activity [43]. Consistently, we have demonstrated the anti-leukemic and anti-plasmodium activities of GSO [24]. Recently, we reported that the hexane extract of GSO was abundant with α-tocopherol (23.0 mg/kg) and β-tocotrienol (70.5 mg/kg) [17,44].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Notably, Eschscholtzxanthin is one of the red pigment carotenoids that is synthesized in the leaves of several plants as a response to photoinhibitory conditions during winter acclimation and displays antioxidant activity [43]. Consistently, we have demonstrated the anti-leukemic and anti-plasmodium activities of GSO [24]. Recently, we reported that the hexane extract of GSO was abundant with α-tocopherol (23.0 mg/kg) and β-tocotrienol (70.5 mg/kg) [17,44].…”
Section: Discussionsupporting
confidence: 80%
“…The GSO obtained was decolorized with activated charcoal and stored in a plastic container in the dark at 4 • C for further study. From the chromatographic analyses, we found that the GSO contained linoleic acid, palmitic acid and oleic acid (69.95%, 6.14% and 10.47% of total fatty acids, respectively), with a n3/n6 ratio of 1:224; α-tocopherol (23.0 mg/kg); β-tocopherol (1.5 mg/kg); γ-tocopherol (1.4 mg/kg); β-tocotrienol (70.5 mg/kg); δ-tocotrienol (17.4 mg/kg) and γ-tocotrienol (4.0 mg/kg) [24].…”
Section: Preparation Of Gso Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified compounds as shown in Figure 1 were assorted into different chemical classes. Identification of the compounds was achieved based on HR-ESIMS data and comparison with literature data as follows: Cis-3-Hexenyl isobutyrate (1) [37], cinnamyl acetate (2) [38], coumaric acid (3) [39], β-sitosterol (4) [39], α-tocopherol (5) [39], linoleic acid (6) [39], palmitic acid (7) [39], stearic acid (8) [39], oleic acid (9) [39], linolenic acid (10) [39], vanillic acid (11) [39], 4-Hydroxybenzaldehyde (12) [39], vanillin (13) [39], syringaldehyde (14) [39], coniferylaldehyde (15) [39], sinapaldehyde (16) [39], abscisic acid (17) [39], cinnamic acid (18) [39], cinnamaldehyde (19) [39], campesterol (20) [39], stigmastanol (21) [39], stigmasterol (22) [39] and quercetin 4 -glucuronide (23) [40]. Guava seed extract provided substantial protection against the ulcerogenic effects of indomethacin in a dose-dependent manner (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The anti-inflammatory, antihypertensive, blood glucose lowering effect, antiviral and cough sedative activities are the key factors which labelled the guava fruit to be a perfect candidate to protect against COVID-19 infection especially for chronic diseased individuals [ 20 ]. Guava seeds (PGE) as a waste product of the commercially important fruit was evaluated as an inhibitor for the proliferation of the human erythroleukemic cells with low toxicity [ 21 ], the seed oil contains unsaturated fatty acids especially, linoleic acid and possessed a high antioxidant activity [ 22 ]. In addition to seed fatty acids, the seeds were found to be rich with proteopolysaccharides with potent anti-inflammatory and immunomodulatory effects [ 23 ], peptides from guava seeds were reported to perform antimicrobial effects against gram-negative bacteria [ 24 ], the phenolic content of the seeds extracted by supercritical fluid extraction performed a high antioxidant activity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%